2010
DOI: 10.1007/s13238-010-0096-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of SELEX-derived ZAP-binding RNA aptamers suggest that the binding specificity is determined by both structure and sequence of the RNA

Abstract: The zinc-finger antiviral protein (ZAP) is a host factor that specifically inhibits the replication of certain viruses, including murine leukemia virus, Sindbis virus and Ebola virus, by targeting the viral mRNAs for degradation. ZAP directly binds to the target viral mRNA and recruits the cellular RNA degradation machinery to degrade the RNA. No significant sequence similarity or obvious common motifs have been found in the so far identified target viral mRNAs. The minimum length of the target sequence is abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…However, alignment of HBV ZRE with other individual viral ZREs did not reveal any obvious sequence homology (data not shown), suggesting that a mysterious secondary or tertiary RNA structure may define the common feature of ZRE. A recent SELEX (Systematic Evolution of Ligands by Exponential Enrichment) study showed that ZAP-binding aptamers that were 40-nt-long G-rich RNAs with stem-loop structures containing conserved “GGGUGG” and “GAGGG” motifs in the loop region [75]. Interestingly, HBV ZRE contains a stem-loop region (epsilon (Δ), nt 1849–1909) which serves as the pgRNA encapsidation signal and as the priming template for virus reverse transcription [6], [7], [76].…”
Section: Discussionmentioning
confidence: 99%
“…However, alignment of HBV ZRE with other individual viral ZREs did not reveal any obvious sequence homology (data not shown), suggesting that a mysterious secondary or tertiary RNA structure may define the common feature of ZRE. A recent SELEX (Systematic Evolution of Ligands by Exponential Enrichment) study showed that ZAP-binding aptamers that were 40-nt-long G-rich RNAs with stem-loop structures containing conserved “GGGUGG” and “GAGGG” motifs in the loop region [75]. Interestingly, HBV ZRE contains a stem-loop region (epsilon (Δ), nt 1849–1909) which serves as the pgRNA encapsidation signal and as the priming template for virus reverse transcription [6], [7], [76].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Huang et al investigated aptamers capable of bind zinc-finger antiviral protein responsible for, inter alia, inhibition of Ebola virus replication. Selected aptamers contained conserved sequences “GGGUGG” and “GAGGG” in the loop region, which was important for specific interaction between aptamer and antiviral protein [ 111 ]. This information could serve as a base to design molecular diagnostic tests capable to detect Ebola mRNA.…”
Section: Aptamers Against Ebola Infectionmentioning
confidence: 99%
“…With the aim to identify RNA sequences that could be a target of ZAP, Huang et al used aptamer technology identifying G-rich RNA aptamers that contained conserved “GGGUGG” and “GAGGG” motifs in the loop region. Interestingly, overexpression of the aptamers significantly reduced ZAP’s antiviral activity and the substitution of the conserved motifs of the aptamers significantly impaired their ZAP-binding ability and ZAP-antagonizing activity, suggesting that the RNA sequence is important for specific interaction between ZAP and the target RNA [188]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%